(3GdJagje dChGFd UfGYI GdJfLjes - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s ((3HdOI GdSeGhI GdYQGb s)
(3ChdgG (B:s
(3hHYO , aEf GdEMGWI HgjFI GdYGde , hcjajI Tcd GdSeGA hGdCQV heG HjfgeG , Ydi hLg GdCNHGQ GdeCNhPI HGdJbdjO fGaYI LOkG s
(3BNQgG (B:s
(3hef JYOGgG abO YQV faSg hUfGYJg deG HdZJ Edjg , dCf ef GdSNQjI hGdESJgRGA , abO LgdgG GdefJSHhf EdjgG , aVdkG Yf GdefJaYjf HgG hGddg GdeSJYGf , fLR HMeO Gddg s
(3Vef eLehY s
(3Cdag GdeDda SfI (B421(3g`s
(3gPg GdfSNI fbdJ ef fSNI cJHJ ai HdO TGPHGN HfjSGHhQ SfI (B573(3g`s
(3HgG YOO ef GdLOGhd hGdQShes
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3Gdadcs